2005
DOI: 10.1098/rspb.2005.3172
|View full text |Cite
|
Sign up to set email alerts
|

Social learning of floral odours inside the honeybee hive

Abstract: A honeybee hive serves as an information centre in which communication among bees allows the colony to exploit the most profitable resources in a continuously changing environment. The best-studied communication behaviour in this context is the waggle dance performed by returning foragers, which encodes information about the distance and direction to the food source. It has been suggested that another information cue, floral scents transferred within the hive, is also important for recruitment to food sources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 22 publications
2
137
1
2
Order By: Relevance
“…In this case, harnessed bees could not have learned to approach the odour during conditioning, thus showing that transfer between situations did indeed exist. The possible natural function of this transfer ability may be related to the observation that bees do indeed learn to associate odours and nectar reward within the hive during trophallaxis with returning foragers (Farina et al, 2005;Gil and De Marco, 2005), and subsequently choose the odour learnt within the hive in a foraging context (von Frisch, 1946;Arenas et al, 2007). Most importantly, these experiments also showed that after the formation of an odour-sucrose association, the learnt odour had acquired a positive/attractive nature for the animal.…”
Section: Discussionmentioning
confidence: 74%
“…In this case, harnessed bees could not have learned to approach the odour during conditioning, thus showing that transfer between situations did indeed exist. The possible natural function of this transfer ability may be related to the observation that bees do indeed learn to associate odours and nectar reward within the hive during trophallaxis with returning foragers (Farina et al, 2005;Gil and De Marco, 2005), and subsequently choose the odour learnt within the hive in a foraging context (von Frisch, 1946;Arenas et al, 2007). Most importantly, these experiments also showed that after the formation of an odour-sucrose association, the learnt odour had acquired a positive/attractive nature for the animal.…”
Section: Discussionmentioning
confidence: 74%
“…The acquisition of associative memories through a social interaction has already been shown or suggested in other social insects [honeybees (Farina et al, 2005;Farina et al, 2007;Gil and De Marco, 2005;Grüter et al, 2006); stingless bees (McCabe and Farina, 2009)], but its functional value in the context of food searching has not been proved before. In bees, the memories established during trophallaxis have been evaluated through a classical paradigm based on the proboscis extension reflex (PER) (Takeda, 1961;Bitterman et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, many learning-related behaviours have been studied in the context of trophallactic interaction, particularly in bees (Farina et al, 2005;Farina et al, 2007;Gil and De Marco, 2005;Martinez and Farina, 2008). The acquisition of these memories is considered as social learning, defined as individual learning that takes place in a social context (Heyes, 1993;Brown and Laland, 2003;Leadbeater and Chittka, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We cannot fully review the many published studies here or in Table 1 but do point to experiments that illustrate a variety of valuable approaches to field sociallearning experiments. For example, demonstrators can be created by feeding them scented foods (Farina, Grüter, & Díaz, 2005) or training them to particular locations (Gould, 1975b). Social cues such as the waggle dance can be modified or eliminated in many ways-for example, by manipulations of the optical or light environment (Esch, Zhang, Srinivasan, & Tautz, 2001;Sherman & Visscher, 2002).…”
Section: Field Experimentsmentioning
confidence: 99%